Local seed systems and village-level determinants of millet crop diversity in marginal environments of India - Nagarajan, Latha; Smale, Melinda (International Food Policy Research Institute, 2005)
In the subsistence-oriented, semi-arid production systems of Andhra Pradesh and Karnataka, India, the environment is marginal for crop growth and often there is no substitute for millet crops. Across communities, farmers grow thirteen different combinations of pearl millet, sorghum, finger millet, little millet, and foxtail millet varieties, but individual farmers grow an average of only two to three millet varieties per season. The notion of the seed system includes all channels through which farmers acquire genetic materials, outside or in interaction with the commercial seed industry. Data are compiled through household surveys and interviews with traders and dealers in village and district markets. Based on the concept of the seed lot, several characteristics of local seed markets are defined and measured by millet crop, including seed transfer rates for farmer-to-farmer transactions and seed replacement ratios. Most seed transactions appear to be based on money. Seed supply channels differ by improvement status of the genetic material. Econometric results indicate the significance of the seed replacement ratios and seed volumes traded in determining the levels of crop biodiversity managed by communities, in addition to the household, farm and other market-related factors identified by previous studies. These are interpreted as indicators of market strength.